A Gas Target Internal to the LHC for the Study of pp Single-Spin Asymmetries and Heavy Ion Collisions - Colin Barschel; Paolo Lenisa; Alexander Nass; Erhard Steffens (Advances in High Energy Physics)
We discuss the application of an open storage cell as gas target for a proposed LHC fixed-target experiment AFTER@LHC. The target provides a high areal density at minimum gas input, which may be polarized 1H, 2H, or 3He gas or heavy inert gases in a wide mass range. For the study of single-spin asymmetries in pp interaction, luminosities of nearly 1033/cm2 s can be produced with existing techniques.